Analysis of genetic and chemical variability of five Curcuma species based on DNA barcoding and HPLC fingerprints - Chen, Mengying; Sun, Jian; Yao, Hui; Gong, Fuyu; Cai, Long; Wang, Chanyan; Shao, Qingsong; Wang, Zhian (Frontiers in Plant Science, 2023)
The rhizomes of Curcuma species have a long medicinal history in Asia. In China, Curcuma species mainly be utilized to make pharmaceutical products, including C. phaecocaulis, C. aromatica, C. wenyujin, C. kwangsiensis and C. longa. In this study, twenty-four samples were selected to study the genetic and chemical variability among five Curcuma species. The ITS2 and trnK intron gene fragment could distinguish the five Curcuma species clearly. The genetic distance between Curcuma species ranged from 0.0085 to 0.0767 based on the data of ITS2 gene sequences with 32 variation sites, and the genetic distance between Curcuma species ranged from 0.0003 to 0.0194 based on the data of trnK intron gene sequences with 39 variation sites. The differences in chemical composition were computed using the Euclidean distance based on the data of HPLC characteristic peak areas and the content of six key components. Five Curcuma species showed otherness chemical composition characteristics, with the Euclidean distance ranging from 3.9443.373 to 6.9987.149. The C. longa showed the biggest variation compared with other species, with the Euclidean distance above 6.239. Agronomic characteristics of five Curcuma species were analyzed including morphological and volatile oil characteristics. Among the samples of the original plants of Ezhu, the volatile oil yield of W1 was the highest, reached to 105.75 mL per single plant. Among all the samples, J6 showed the highest yield of volatile oil, reached to 149.42 mL per single plant. The results showed that chemical composition similarity of the medicinal plants was the primary proof for the selection of the original plants of the Curcuma medicinal materials. The genetic distance and chemical variability were important references for discovering new medicinal plant resources.